2004
DOI: 10.1086/386293
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in AXIN2 Cause Familial Tooth Agenesis and Predispose to Colorectal Cancer

Abstract: Wnt signaling regulates embryonic pattern formation and morphogenesis of most organs. Aberrations of regulation of Wnt signaling may lead to cancer. Here, we have used positional cloning to identify the causative mutation in a Finnish family in which severe permanent tooth agenesis (oligodontia) and colorectal neoplasia segregate with dominant inheritance. Eleven members of the family lacked at least eight permanent teeth, two of whom developed only three permanent teeth. Colorectal cancer or precancerous lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
568
1
30

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(618 citation statements)
references
References 46 publications
11
568
1
30
Order By: Relevance
“…For example, Lammi et al 2 described a family with nine carriers of a nonsense mutation in AXIN2; the gastrointestinal phenotype in carriers varied from 68 adenomas in a 57-year-old carrier to no adenomas in a 26-year-old and one adenoma in a 58-year-old. Even greater clinical variability was reported by Marvin et al, 3 in terms of the number (from none to more than 100), type (adenomatous or hyperplastic) and location (colonic or gastric) of polyps, and the presence of neoplasias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lammi et al 2 described a family with nine carriers of a nonsense mutation in AXIN2; the gastrointestinal phenotype in carriers varied from 68 adenomas in a 57-year-old carrier to no adenomas in a 26-year-old and one adenoma in a 58-year-old. Even greater clinical variability was reported by Marvin et al, 3 in terms of the number (from none to more than 100), type (adenomatous or hyperplastic) and location (colonic or gastric) of polyps, and the presence of neoplasias.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of cases negative for APC and MUTYH mutations, Renkonen et al, 8 described an AXIN2 mutation in a family with previously reported oligodontia. 2 Mongin et al 9 described 38 patients with adenomas or serrated polyps in which AXIN2 screening gave negative results. In light of these studies, it is likely that the number of polyposis patients who have undergone testing for AXIN2 alterations is still insufficient to define the role of the gene in familial polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations in the levels of Axin, APC, β-catenin, LEF1 or TCF4, for example, contribute to the initiation and/or progression of several different types of cancer [7][8][9][10][11][12]. It is therefore not surprising that so much effort has gone into the development of new drugs based on our knowledge of Wnt signaling to treat disease.…”
Section: Canonical Wnt Signalingmentioning
confidence: 99%
“…The proband was 19 years old at the time of inclusion (patient B II-3) with severe TA missing 12 permanent teeth (17,13,11,21,23,24,27,32,33,34,35,37,42,43,44,47). The upper anterior teeth show a conical aspect and the permanent upper first molars are hypoplastic.…”
Section: Family Bmentioning
confidence: 99%
“…Clinical examination proband. In her permanent dentition, she has severe TA of 23 teeth (17, 15, 14 (16,13,23, 33 and 46), two of which have a conical shape and one being hypoplastic. Although her mandible is also retruded, leading to a convex profile, the dished-in appearance is again the most catching feature in her facial profile.…”
Section: Family Cmentioning
confidence: 99%